Developing redundant binary representations for genetic search - Fonseca, C. M. (2012)
This paper considers the development of redundant representations for evolutionary computation. Two new families of redundant binary representations are proposed in the context of a simple mutationselection evolutionary model. The first is a family of linear encodings in which the connectivity of the search space may be designed directly via a decoding matrix. The second is a family of representations exhibiting various degrees of neutrality, and is constructed using mathematical tools from error-control coding theory. The study of these representations provides additional insight into the properties of redundant encodings, such as synonymity, locality, and connectivity, and into their interrelationships.